Digging for clues: Stick tools used for honey digging in a second community of ‘forest fragment chimpanzees’ outside the Budongo and Bugoma Forests, Uganda - Matthew R. McLennan; Georgia A. Lorenti; Simon Mugenyi; Jonan Muganzi; Jacqueline Rohen (Revue de Primatologie)
Chimpanzees (Pan troglodytes) are one of the most frequent tool users among nonhuman primates. Documenting tool use in newly-studied chimpanzee populations, and identifying technological variation among regional groups (‘communities’), aids understanding of the behavioural and ‘cultural’ diversity of this species. Some chimpanzee populations use sticks to dig out subterranean nests of stingless bees (Meliponini) to access the underground honey stores, a tool-assisted foraging behaviour referred to here as ‘honey digging’. Honey digging has been reported mostly from sites in Central and West-Central Africa, and appears less common in East Africa. Chimpanzees in mid-western Uganda have unusually small tool repertoires. In particular, well-studied chimpanzees in Uganda’s Budongo Forest famously do not use stick tools in foraging. However, honey digging was found to occur in the Bulindi community, which inhabit remnant fragments of riverine forest between the main Budongo and Bugoma forests. Previously, it was unclear if this technology was unique to the Bulindi community among chimpanzee communities within the greater Budongo–Bugoma landscape. Here, we show that honey digging with sticks occurs in a second group of ‘forest fragment chimpanzees’ (known as the Mairirwe community) that also range outside the Budongo and Bugoma forests. Digging (or ‘perforating’) sticks recovered at two Meliponini ground nests in Mairirwe were remarkably similar in dimensions to digging sticks from Bulindi. Sticks used by these two nearby Ugandan populations were also similar to honey digging sticks used by chimpanzees in Central Africa, suggesting relative uniformity in this tool use behaviour across a large geographical area. Our study also showed that chimpanzees in Mairirwe compete with humans for this underground resource, with local people using machetes to excavate the bee nests. Our data suggest that tool-assisted honey digging may be a foraging behaviour common to chimpanzees inhabiting riverine forest fragments outside the Budongo and Bugoma forests. This study also underscores the importance of considering populations surviving in degraded human-modified habitats outside Uganda’s main forest blocks, such as the Mairirwe and Bulindi communities, in regional models to explain variation in chimpanzee tool use.